RESEARCH ON THE PRE-TRAVEL BEHAVIOR OF THE BULGARIAN TRAVELERS (International Journal of Innovative Technologies in Economy, 2023)
This research paper explores and discusses the behavior of the Bulgarian non-organized travelers concerning their travel destination and accommodation choices before the pandemic period. Another study goal of the paper is to identify the typical segment profiles of the Bulgarian travelers. The main research method was a content analysis of the information from the open-ended questions to the members of a closed Bulgarian group “Travelling in the world” in Facebook. The survey sample consists of 164 travelors who responded on a voluntary basis to questions related to their pre-travel behavior. Additional primary information was derived from the comments of the group members about their travel behavior. Тhe study identified 3 main segments among the Bulgarian travelers with different pre-travel behavior called by the authors “Comfort Travelers”, “Adventurers” and “Travelers around”. The final part of the paper includes conclusions from the study about the Bulgarian travelers’ behavior on behalf of destination and accommodation choice before the pandemia and some practical suggestions to the hoteliers about using more in-depth surveys with travelers and content marketing for attracting and retaining guests.